What shapes implementation of a school-based makerspace? Teachers as multilevel actors in STEM reforms - Brian E. Gravel; Cassidy Puckett (SpringerOpen, 2023)
Abstract Background We investigate the factors that shape teachers' implementation of a school STEM reform-the creation of a high-school makerspace. Educational reformers have increasing interest in making and makerspaces in schools. Prior research shows how factors shape reform at the classroom, school (organizational), and institutional levels, as well as across levels. However, most research on teachers tends to focus on classroom-level effects, which may not capture the full complexity of how they navigate multilevel reforms. We consider teachers' decision-making from an ecological perspective to investigate what shapes their implementation efforts, using observational and interview data collected over 2 years in a large comprehensive high school. Results We find teachers' efforts are shaped by four "distances"-or spaces teachers traversed, physically and conceptually-related to skillsets and distributed expertise, physical space, disciplinary learning, and structural factors. The distances operate as a constellation of factors-independently identifiable, co-operatively manifesting-to shape implementation. We position teacher deliberations and decision-making as portals into the forms of organizational and institutional supports offered in multilevel reforms. Conclusions The paper contributes insights into makerspace implementation in schools, adding to the emerging literature on how making can transform STEM learning experiences for students. We conclude that teachers' decision-making around multilevel implementations can inform our understanding of how makerspaces are implemented and their impact on students' experiences, as well as how seeing teachers as multilevel actors can offer new insights into reform dynamics writ large. We offer implications for makerspaces in schools, as well as methodological and theoretical considerations for how organizations and institutions can better support teachers as agents of STEM reform.